The Development of an Online Food Ordering System for JomMakan Restaurant - AZAHARI, MUHAMMAD HAIQAL; HAMID ALI, FIRKHAN ALI (Applied Information Technology And Computer Science, 2022)
This Food Ordering Online System was created to address the issue of those who do not have access to a vehicle or do not have the time to go out and buy their own food. It is a website that will assist people in purchasing halal cuisine from restaurants in Setiawangsa, Kuala Lumpur. The web-based was created using a prototyping-based technique that resulted in a two-phase prototype that was then turned into a complete web-based. HTML, CSS, Javascript, and PHP will be used to create this website. This project employs a technique known as prototype approach. Initial plan, create prototype, customer validation, iterate prototype, repeat stages until no more iterations are needed, and ultimately launch the website are the phases. We inject a Geolocation API into the website to obtain the user’s and technicians’ specific locations, which aids the code in producing exact results. Overall, it may be an efficient alternative to a restaurant by lowering time consumption, decreasing human mistakes, and offering high-quality customer service.